Jednostka, neoliberalizm i redukcjonizm edukacji współczesnej - Gromkowska-Melosik, Agnieszka (Studia Edukacyjne, 2020)
Contemporary educational policy of many developed countries is permeated with the ideology of neoliberalism, the essence of which is to increase the efficiency and "focus on the best," while respecting the principle of indifference to sex, race or social origin. It is belevied that in neoliberalism, education - seen as the "good of the individual" is bringing economic benefits to society. Learning / knowledge becomes a commodity, an individual is treated in accordance with the logic of neoliberalism as "innovative entrepreneur", which determines his/her own success or failure. Here there is a dominance of rhetoric of performance, efficiency and standards together with conviction that schools should operate as excellent corporations that bring profits through routine activities, procedures, diagnosis and evaluation. In this context one can ask the question: is it still possible, to believe in emancipatory function of education?